2010
DOI: 10.2319/102809-604.1
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of torque expression between stainless steel, titanium molybdenum alloy, and copper nickel titanium wires in metallic self-ligating brackets

Abstract: Stainless steel has the largest torque expression, followed by TMA and then NiTi.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 12 publications
2
34
0
4
Order By: Relevance
“…2016; 11(2):e5967. (28)(29)(30)(31)(32)(33)(34), none of the studies took into account the curved section of the arch as simulation models were done using straight pieces of wire. In the absence of in-vivo studies, extrapolating, the result so obtained, to various clinical settings may not be accurate for any given bracket and archwire combination.…”
Section: Discussionmentioning
confidence: 99%
“…2016; 11(2):e5967. (28)(29)(30)(31)(32)(33)(34), none of the studies took into account the curved section of the arch as simulation models were done using straight pieces of wire. In the absence of in-vivo studies, extrapolating, the result so obtained, to various clinical settings may not be accurate for any given bracket and archwire combination.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, optimal treatment outcomes require effective torque expression, which is sensitive to irregularities in tooth anatomy, the size, morphology, and engagement of the archwire in the bracket, as well as the position, material properties, and slot size of the bracket (11)(12)(13)(14)(15)(16)(17). For example, although 0.22-inch brackets might be outperform 0.018-inch in some clinical aspects like sliding mechanics, they are inferior in torque expression (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…The response variables in the research were: torques of the mentioned teeth (13,23,14,24,15,25,16,26) and widths between pairs of teeth of the same kind (canines, first premolars, second premolars and first molars), measured before and after the treatment (T0 and T1).…”
Section: Discussionmentioning
confidence: 99%
“…As Zachrisson [6] said, torque control is one of the weaknesses of the preadjusted bracket systems [6]. And, as many authors have suggested, the expression of torque is the result of interaction of many factors [9,11,24]. In this research, variables, such as individual biological variation, the deformation of the slot of the bracket during treatment, the amount of resin between the bracket base and the tooth, possible defects in wires and brackets or the starting torque of the posterior teeth, could not be controlled.…”
Section: Analysis Of T0 To T1 Changes In Torque According To the Techmentioning
confidence: 99%